Quality Management System In Construction - Mohammed, Abdul Hakim; Abdullah@ Asmoni, Mat Naim (2006)
This paper describes the Quality Management System (QMS) concept and its application in the construction industry. A misunderstanding among the construction players on the QMS concept has become the stumbling block for its successful implementation.